2003
DOI: 10.1172/jci17741
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal degeneration and mitochondrial dysfunction

Abstract: Over the last decade, the underlying genetic bases of several neurodegenerative disorders, including Huntington disease (HD), Friedreich ataxia, hereditary spastic paraplegia, and rare familial forms of Parkinson disease (PD), Alzheimer disease (AD), and amyotrophic lateral sclerosis (ALS), have been identified. However, the etiologies of sporadic AD, PD, and ALS, which are among the most common neurodegenerative diseases, are still unclear, as are the pathogenic mechanisms giving rise to the various, and ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
185
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(195 citation statements)
references
References 65 publications
8
185
0
2
Order By: Relevance
“…Not surprisingly, neurons are exquisitely sensitive to perturbations of mitochondrial function. Impaired mitochondrial energy metabolism has been implicated in numerous heritable neurological disorders as well as neurodegenerative diseases, including Huntington, Parkinson, and Alzheimer disease (51)(52)(53). PGC-1␣ is abundantly expressed in the brain and its deficiency leads to degenerative lesions in several brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, neurons are exquisitely sensitive to perturbations of mitochondrial function. Impaired mitochondrial energy metabolism has been implicated in numerous heritable neurological disorders as well as neurodegenerative diseases, including Huntington, Parkinson, and Alzheimer disease (51)(52)(53). PGC-1␣ is abundantly expressed in the brain and its deficiency leads to degenerative lesions in several brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the role of functional imaging with FDG PET would not be so important if the results of two decades of investigation into the molecular genetics and pathophysiology of brain disorders had not clearly demonstrated that degeneration occurs preferentially at the synaptic level and involves dysfunction in mitochondrial energy metabolism [31][32][33]. For this reason, this technique is nowadays considered the most appropriate approach to track local energetic transformation in the living human brain [34].…”
Section: Baruch Spinozamentioning
confidence: 99%
“…1). Increasing evidence has implicated mitochondrial dysfunction as a critical mechanism underlying the pathologic development of many progressive neurodegenerative disorders, including Alzheimer disease, Parkinson disease, amyotrophic lateral sclerosis, and Huntington diseases (2)(3)(4)(5)(6).…”
mentioning
confidence: 99%
“…In the central nervous system, phospholipase A 2 s (PLA 2 s) 3 play critical roles in cellular growth, lipid homeostasis, and second messenger generation (8,9). PLA 2 s catalyze the cleavage of acyl groups from glycerophospholipids, generating free fatty acids and lysophospholipids, thereby initiating dual pathways of signal transduction (10).…”
mentioning
confidence: 99%